Ruang Terbuka Hijau untuk Ruang Publik di Palangka Raya: Tantangan Implementasi Kebijakan dan Manajemen Strategis - Alim, Bimantara Nur; Andreastuti, Desie (SERUNAI, 2025)
Green Open Space (GOS) plays a crucial role in creating sustainable urban settlements, offering ecological, social, and economic benefits. In Palangka Raya, GOS serves as a public space that enhances environmental quality, promotes social interactions, and provides recreational opportunities. However, the implementation of GOS policies faces various challenges, including inadequate urban planning, lack of coordination among stakeholders, and insufficient facilities. This study aims to analyze the management of GOS as a public space by examining policy implementation challenges and strategic management approaches. Using a qualitative descriptive method, the study explores policy frameworks, government regulations, and urban management strategies. The findings indicate that the lack of coordination between municipal authorities and limited public participation hinder effective GOS development. Additionally, the absence of a comprehensive strategic management approach affects the sustainability of green spaces. Urban expansion and land-use changes further threaten the availability of GOS, reducing its accessibility for the community. Moreover, the lack of financial resources and maintenance strategies leads to deteriorating infrastructure in existing GOS areas. The research suggests that local governments should strengthen evidence-based policies, enhance inter-agency coordination, and integrate strategic management frameworks to ensure the sustainability of GOS. This study contributes to the discourse on urban sustainability by providing recommendations for improving GOS governance and strategic planning in Palangka Raya. Future research should explore innovative solutions, including smart urban planning and public-private partnerships, to enhance the quality and accessibility of GOS.